CIITA stimulation of transcription factor binding to major histocompatibility complex class II and associated promoters in vivo - Wright, Kenneth L. (The National Academy of Sciences, 1998)
CIITA is a master transactivator of the major histocompatibility complex class II genes, which are involved in antigen presentation. Defects in CIITA result in fatal immunodeficiencies. CIITA activation is also the control point for the induction of major histocompatibility complex class II and associated genes by interferon-γ, but CIITA does not bind directly to DNA. Expression of CIITA in G3A cells, which lack endogenous CIITA, followed by in vivo genomic footprinting, now reveals that CIITA is required for the assembly of transcription factor complexes on the promoters of this gene family, including DRA, Ii, and DMB. CIITA-dependent promoter assembly occurs in interferon-γ-inducible cell types, but not in B lymphocytes. Dissection of the CIITA protein indicates that transactivation and promoter loading are inseparable and reveal a requirement for a GTP binding motif. These findings suggest that CIITA may be a new class of transactivator.